Obesity as a risk factor for sedation-related complications during propofol-mediated sedation for advanced endoscopic procedures - Azar, Riad (2011)
Background There are limited data on the safety of anesthesia-assisted endoscopy by using propofol-mediated sedation in obese individuals undergoing advanced endoscopic procedures (AEPs). Objective To study the association between obesity (as measured by body mass index [BMI]) and the frequency of sedation-related complications (SRCs) in patients undergoing AEPs. Design Prospective cohort study. Setting Tertiary referral center. Patients A total of 1016 consecutive patients undergoing AEPs (BMI <30, 730 [72%]; 30-35, 159 [16%]; >35, 127 [12%]). Intervention Monitored anesthesia sedation with propofol alone or in combination with benzodiazepines and/or opioids. Main Outcome Measurements SRCs, airway maneuvers (AMs), hypoxemia, hypotension requiring vasopressors, and early procedure termination were compared across 3 groups. Results There were 203 AMs in 13.9% of patients, hypoxemia in 7.3%, need for vasopressors in 0.8%, and premature termination in 0.6% of patients. Increasing BMI was associated with an increased frequency of AMs (BMI <30, 10.5%; 30-35, 18.9%; >35–26.8%; P < .001) and hypoxemia (BMI <30, 5.3%; 30-35, 9.4%; >35, 13.4%; P = .001); there was no difference in the frequency of need for vasopressors (P = .254) and premature termination of procedures (P = .401). On multivariable analysis, BMI (odds ratio [OR] 2.0; 95% CI, 1.3-3.1), age (OR 1.1; 95% CI, 1.0-1.1), and American Society of Anesthesiologists class 3 or higher (OR 2.4; 95% CI, 1.1-5.0) were independent predictors of SRCs. In obese individuals (n = 286), there was no difference in the frequency of SRCs in patients receiving propofol alone or in combination (P = .48). Limitations Single tertiary center study. Conclusions Although obesity was associated with an increased frequency of SRCs, propofol sedation can be used safely in obese patients undergoing AEPs when administered by trained professionals.